Association between exposure to ambient air pollution before conception date and likelihood of giving birth to girls in Guangzhou, China. (December 2015) - Lin, Hualiang; Liang, Zhijiang; Liu, Tao; Di, Qian; Qian, Zhengmin; Zeng, Weilin; Xiao, Jianpeng; Li, Xing; Guo, Lingchuan; Ma, Wenjun; Zhao, Qingguo
Abstract: A few studies have linked ambient air pollution with sex ratio at birth. Most of these studies examined the long-term effects using spatial or temporal comparison approaches. This study aimed to investigate whether parental exposure to air pollution before conception date could affect the likelihood of the offspring being male or female. We used the information collected in a major maternal hospital in Guangzhou, China. The parental exposure to air pollution was assessed using the air pollution concentration before the conception date. Logistic regression models were used to assess the association between air pollution exposure and birth sex with adjustment for potential confounding factors, such as maternal age, parental education levels, long-term trend, season, and weather condition (mean temperature and relative humidity). The analysis revealed that higher air pollution was associated with higher probability of female newborns, with the effective exposure around one week prior to conception date. In the one-pollutant models, PM10, SO2 and NO2 had significant effects. For example, the excess risk was 0.61% (95% confidence interval (95% CI): 0.36%, 0.86%) for a 10 ug/m 3 increase in lag 2 day's PM10, 0.42% (95% CI: 0.21%, 0.64%) for lag 3 day's SO2 and 0.97% (95% CI: 0.44%, 1.50%) for lag 3 day's NO2 ; and in two-pollutant models, PM10 remained statistically significant. These results suggest that parental exposure to ambient air pollution a few days prior to conception might be a contributing factor to higher probability of giving birth to female offspring in Guangzhou. Graphical abstract: Highlights: We compared air pollution exposures of parents of boys and girls in Guangzhou. Air pollution exposure was associated with higher chance of giving birth to girls. Exposure of about one week before conception date was effective for this effect.